2013
DOI: 10.1002/pmic.201200001
|View full text |Cite
|
Sign up to set email alerts
|

The acetylproteome of Gram‐positive model bacterium Bacillus subtilis

Abstract: N(ε) -lysine acetylation, a reversible and highly regulated PTM, has been shown to occur in the model Gram-negative bacteria Escherichia coli and Salmonella enterica. Here, we extend this acetylproteome analysis to Bacillus subtilis, a model Gram-positive bacterium. Through anti-acetyllysine antibody-based immunoseparation of acetylpeptides followed by nano-HPLC/MS/MS analysis, we identified 332 unique lysine-acetylated sites on 185 proteins. These proteins are mainly involved in cellular housekeeping function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
107
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(114 citation statements)
references
References 45 publications
7
107
0
Order By: Relevance
“…Specifically, the function of the proteins identified as acetylation targets has not been analyzed in vitro to identify the modifying enzymes or whether or not acety- Ac , number of identified acetylated proteins; % Total Ac , percentage of acetylated proteins of the entire proteome; N, no; Y, yes. *, values are different than those previously reported; however, the values listed reflect the available data that were obtained from supplementary information from the cited references (28,142,143,(153)(154)(155)(156)(157)(158)(159)(160)(161). The percent scale at the top should be used to estimate the percentage of acetylated proteins in each of the categories within any given microorganism shown.…”
Section: Bacterial Acetylome Studiesmentioning
confidence: 62%
See 1 more Smart Citation
“…Specifically, the function of the proteins identified as acetylation targets has not been analyzed in vitro to identify the modifying enzymes or whether or not acety- Ac , number of identified acetylated proteins; % Total Ac , percentage of acetylated proteins of the entire proteome; N, no; Y, yes. *, values are different than those previously reported; however, the values listed reflect the available data that were obtained from supplementary information from the cited references (28,142,143,(153)(154)(155)(156)(157)(158)(159)(160)(161). The percent scale at the top should be used to estimate the percentage of acetylated proteins in each of the categories within any given microorganism shown.…”
Section: Bacterial Acetylome Studiesmentioning
confidence: 62%
“…Bacterial acetylomes have been characterized in E. coli (141,142), S. enterica (153), Bacillus subtilis (154), Erwinia amylovora (155), R. palustris (28), Staphylococcus aureus (156), Geobacillus kaustophilus (157), Vibrio parahaemolyticus (158), Thermus thermophilus (159), M. tuberculosis (143), Mycoplasma pneumoniae (160), and Streptomyces roseosporus (161). These studies have identified a range of 62 to 667 putatively acetylated proteins per organism, with the majority of acetylated proteins being involved in central metabolism and translation (141,156,158) (Fig.…”
Section: Bacterial Acetylome Studiesmentioning
confidence: 99%
“…It was found that many enzymes involved in the amino acid metabolism were lysine-acetylated in E. coli (30,31), S. enterica (32), B. subtilis (33), Geobacillus kaustophilus (34), Thermus thermophiles (35), Saccharopolyspora erythraea (36), and Saccharomyces cerevisiae (37). On the other hand, most of the ACT domain-containing proteins appear to interact with amino acids and are involved in some aspect of regulation of amino acid metabolism in E. coli, including serine binding to 3-phosphoglycerate dehydrogenase, which catalyzes the first step in the biosynthesis of serine; phenylalanine binding to chorismate mutase, which catalyzes the first two steps in the biosynthesis of phenylalanine; valine binding to acetohydroxyacid synthase, which is involved in biosynthesis of branched chain amino acids; lysine binding to aspartokinase, which catalyzes the first step in the biosynthesis of methionine, lysine, and threonine; isoleucine and valine binding to threonine deaminase involved in biosynthesis of branched chain amino acids; threonine binding to homoserine dehydrogenase, which catalyzes the third step in the aspartate pathway; leucine binding to isopropylmalate synthase, which catalyzes the first committed step in the leucine biosynthetic pathway; and histidine binding to ATP phosphoribosyltransferase, which catalyzes the first and committed step in histidine biosynthesis (8,9).…”
Section: Discussionmentioning
confidence: 99%
“…The large collection of N‐acyl‐transferase genes present in the genome (46 genes) and often with no identified function should be explored for this type of function. Among those are also safeguard systems that protect residues within proteins (usually lysine residues, but also arginine or histidine residues) against spurious modification by reactive metabolic intermediates (Kim et al ., 2013). Interestingly, as is commonplace in evolution processes, once a programmed modification exists, it can be recruited for further functions, in particular regulatory functions (Kosono et al ., 2015).…”
Section: Bacillus Subtilis In 2017mentioning
confidence: 99%